Efeitos do processo de convergência contábil no imposto de renda das pessoas jurídicas: os limites impostos pelo conceito de renda e pelo princípio da proteção da confiança - Roberto da Motta Salles Carvalho de Lopes (2014)
The Accounting Harmonization Process, based on the adoption of internationally accepted accounting standards (the International Financial Reporting Standards – IFRS), began to be legally implemented, in Brazil, with the enacting of Law #11.638/2007. The process ocurred in a context of general lack of trust in the financial statements. The changes caused by this process on the accounting rules are remarkable and affect fundamental principles such as the historic cost. The substance over form principle and the fair value become more important but at the same time increase the subjectivity in the utilization of accounting rules. Changes in accounting rules have the potential to cause tax effects, specially in regard to taxpayers that use the real profit method for purposes of the Corporate Income Tax, since the assessment of the taxable basis begins with the accounting net income. The constitutional concept of income and the definition of income as per the National Tax Code – NTC become important sources of limits for the tax changes that may derive from the changes in accounting. To ensure that accounting changes would be tax neutral, as promised since the beginning of congressional procedures, Federal Government undertook several measures in a row, including the adoption of a Transitional Tax Regime – TTR which put tax rules safe from accounting changes. The analysis is focused on the limits that must be imposed to tax consequences derived from accounting changes, in view of the constitutional income concept and the definition of income given by NTC as well as per the protection of trust principle. It is concluded that the constitutional concept of income and the definition of income provided by the NTC prohibit accounting changes based on the substance over form principle to cause tax effects and also prohibit that, under certain circumstances, fair value generate tax effects. It is also concluded that protection of trust principle prohibits tax authorities to take any measure aiming at an increase of the taxpayers tax burden in regard to transactions occurred under the TTR, the TTR itself being construed as a form of protection of trust.